Machiavellian Traits, Locus of Control, and Ministry of Finance Supervision: Influence on Auditor Dysfunction - Muhammad Ramadhan Kenoriza; Slamet Wahyudi (Eduvest - Journal of Universal Studies, 2025)
Auditor dysfunction directly affects audit quality, necessitating efforts to minimize its triggers and foster a professional work environment. This study aims to analyze the influence of Machiavellian traits, locus of control, and the effectiveness of the Ministry of Finance’s coaching and supervision program on dysfunctional auditor behavior. This research is classified as quantitative research. The data collection method employed is primary data, utilizing a questionnaire distribution approach. Questionnaires were distributed to 148 external auditor respondents working at Public Accounting Firms in the South Jakarta area. The sampling technique used was non-probability sampling. The results of this study indicate, in part, that Machiavellian traits have a positive and significant effect on dysfunctional auditor behavior, locus of control has a negative and significant effect on dysfunctional auditor behavior, and the Ministry of Finance of the Republic of Indonesia’s coaching and supervision program has a positive and significant effect on reducing dysfunctional auditor behavior.